2016
DOI: 10.1021/acs.jnatprod.5b00922
|View full text |Cite
|
Sign up to set email alerts
|

Methylbenzene-Containing Polyketides from a Streptomyces that Spontaneously Acquired Rifampicin Resistance: Structural Elucidation and Biosynthesis

Abstract: Conventional screening for novel bioactive compounds in actinomycetes often results in the rediscovery of known compounds. In contrast, recent genome sequencing revealed that most of the predicted gene clusters for secondary metabolisms are not expressed under standard cultivation conditions. To explore the potential metabolites produced by these gene clusters, we implemented a cryptic gene activation strategy by screening mutants that acquire resistance to rifampicin. The induction of rifampicin resistance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Previously, Thong et al [35] found two closely related compounds of 1-4, and they were isolated from a Streptomyces that had been spontaneously acquired rifampicin resistance. These compounds contained E-olefins and have both a methylbenzene unit and a 2-amino-3-hydroxycyclopent-2-enone (C 5 N) moiety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, Thong et al [35] found two closely related compounds of 1-4, and they were isolated from a Streptomyces that had been spontaneously acquired rifampicin resistance. These compounds contained E-olefins and have both a methylbenzene unit and a 2-amino-3-hydroxycyclopent-2-enone (C 5 N) moiety.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the presence of a carboxylic acid moiety in the novel compounds, and a C 5 N moiety in the known compounds, may not be involved in the antimicrobial activity. Based on draft genome sequences of the rifampicin-resistant mutant (TW-R50-13), the methylbenzene moiety may be biosynthesized by the expression of polyketide synthase (PKS) genes that are located at a different locus from the biosynthetic genes for the C 5 N moiety [35]. The genes encoding for PKS have been disclosed to complex biosynthetic mechanisms, which were involved in the production of many metabolites in microorganisms [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phylogenetic tree was constructed using the Maximum Likelihood (ML) method applied to pairwise sequence distances calculated by the general time reversible (GTR) model with the MEGA program [ 31 , 32 ]. In addition, partial rpoB gene of antifungal isolates was obtained by PCR amplification using a primer set for rpoB -P2 [ 33 ] and purification, and sequenced. Additional phylogenetic tree of the concatenated sequences of 16S rRNA and rpoB genes was constructed using the ML method and GTR model.…”
Section: Methodsmentioning
confidence: 99%
“…In the light of huge sequence data in the genomic era, several main strategies have been developed in an attempt to harness this tremendous chemical diversity. These include promoter engineering (Li et al, 2017 ), diversification of culture conditions (Zhang et al, 2014 ), ribosome engineering (Wang et al, 2008 ; Thong et al, 2016 ), manipulation of regulators (Chen et al, 2017 ), and others. Among them, promoter engineering has been proved as a powerful and efficient method to activate or improve the biosynthesis of interest products (Li et al, 2015 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%